2013
DOI: 10.1111/j.1708-8305.2012.00677.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Mediterranean Spotted Fever Rickettsia Isolated From a European Traveler in the State of São Paulo, Brazil

Abstract: Rickettsial spotted fever is common in southeastern Brazil. Differential diagnosis of pathogens can be performed with proper laboratory methods. A traveler arriving from Portugal developed a fatal febrile hemorrhagic syndrome diagnosed as spotted fever rickettsiosis. We isolated the agent, which was identified as Rickettsia conorii conorii by sequencing rickettsial genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Interestingly, we have previously reported an imported and fatal case of Mediterranean spotted fever in a Portuguese traveler that arrived at Brazil, which was also confirmed by rickettsial isolation and molecular detection. 13 The recognition that eschar ( tache noire ) as an important clue for diagnosis of some rickettsial diseases was essential for the suspicion of the case presented here. Because of the cross-reactivity of antibody responses to spotted fever group Rickettsia species, 1 clinicians must be aware of the importance of submitting appropriate samples for molecular detection or isolation techniques when available, as serology alone is not sufficient to identify the species responsible for infection.…”
Section: Discussionmentioning
confidence: 84%
“…Interestingly, we have previously reported an imported and fatal case of Mediterranean spotted fever in a Portuguese traveler that arrived at Brazil, which was also confirmed by rickettsial isolation and molecular detection. 13 The recognition that eschar ( tache noire ) as an important clue for diagnosis of some rickettsial diseases was essential for the suspicion of the case presented here. Because of the cross-reactivity of antibody responses to spotted fever group Rickettsia species, 1 clinicians must be aware of the importance of submitting appropriate samples for molecular detection or isolation techniques when available, as serology alone is not sufficient to identify the species responsible for infection.…”
Section: Discussionmentioning
confidence: 84%
“…The case definition of confirmed SFG includes both clinical evidence and laboratory confirmation. The clinical features of this rickettsiosis consist of an acute undifferentiated febrile illness, often accompanied by headache, myalgia and nauseas, and a maculopapular or vesicular rash may be observed a few days after the onset of illness [13][14][15]. When a patient develops a febrile illness, the suspicion for tick-borne illness should be high in those who live or travel to endemic areas.…”
Section: Rickettsioses Caused By the Genus Rickettsia And Their Diagn...mentioning
confidence: 99%
“…The greatest challenge to clinicians is not therapy but the difficult diagnosis during the early phase of infections [18]. The diagnosis of rickettsiosis can be missed because of these nonspecific initial clinical presentations and the absence of specific laboratory confirmation [22]. Serological diagnosis is usually retrospective; antibody increase takes 15-26 days, thus limiting the clinical impact of diagnosis [23].…”
Section: Rickettsioses Caused By the Genus Rickettsia And Their Diagn...mentioning
confidence: 99%
“…The greatest challenge to clinicians is not therapy but the difficult diagnosis during the early phase of infections [37]. The diagnosis of TBD may be masked due to these initial non-specific clinical presentations and the absence of confirmation by specific laboratory testing [38]. In addition, serological diagnosis is usually retrospective; antibody increase takes 15-26 days, thus limiting the clinical impact of diagnosis [39].…”
Section: Introductionmentioning
confidence: 99%
“…The diagnostic test for BSF and ehrlichiosis recommended in Brazil is a dual test for LD [42,46], even though the condition has different immunological and epidemiological aspects than LD. Thus, the analysis of the second stage of the test, western blot, needs a certain number of bands present to be considered positive [38,44]. However, even following this strict criterion, a larger study conducted in Brazil demonstrated a significant number of false positives (16%) [46].…”
Section: Introductionmentioning
confidence: 99%